ANALISIS KAUSALITAS ANTARA RISIKO KREDIT DAN RISIKO LIKUIDITAS PADA BANK BUMN PERIODE 2002-2010 - Tunggul Patar Naibaho; Syarief Fauzie (Departemen Ekonomi Pembangunan USU, 2015)
This study aims to analyze the relationship between the variables of credit risk and liquidity risk on a Indonesian state-owned enterprise bank member which those are Mandiri Bank, BRI Bank, BNI Bank, and BTN Bank. The kind of data which is used in this research is time series of the first quarter of the year 2002 through the fourth quarter of the year 2010 (2002:Q1-2010:Q4) were obtained from the Bank of Indonesia’s official website. The test methods are done by using Unit Root Test, Johansen Cointegration Test, VAR, VECM, and Granger Causality.The result of the study concluded that there is a long-term relationship between credit risk and liquidity risk on Mandiri Bank, BRI Bank, and BNI Bank. There is a one-way relationship between credit risk and liquidity risk on BRI Bank. Credit risk affects liquidity risk. Meanwhile, there are no causalities between credit risk and liquidity risk on Mandiri bank, BNI Bank, and BTN Bank.Keywords : Unit root test, Cointegration test, VAR, VECM, and Granger Causality Test